2021
DOI: 10.5613/rzs.51.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Integration Policies and Public Perceptions of Immigrants in Europe

Abstract: National mechanisms of migrant integration into the host society and the wider social context in which migration occurs may affect the construction of public attitudes towards migrants regardless of their origin or status. By combining the data of two international studies: the Migrant Integration Policy Index (MIPEX) and the European Social Survey (ESS), this paper examines national policies regarding migrant integration and the public perception of migrants in the host society in selected European countries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In line with the competition theory (Quillian, 1995; Semyonov et al, 2006), ethnic majority individuals tend to perceive members of the minority group as a threat to the economic and political systems, especially when they are highly present in a social context with high rates of unemployment (Hjerm, 2009; Markaki & Longhi, 2013). Consequently, these perceptions could also promote less favorable attitudes toward their integration within society, endorsing policies that limit the rights and opportunities granted to the ethnic minority (Gregurović, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the competition theory (Quillian, 1995; Semyonov et al, 2006), ethnic majority individuals tend to perceive members of the minority group as a threat to the economic and political systems, especially when they are highly present in a social context with high rates of unemployment (Hjerm, 2009; Markaki & Longhi, 2013). Consequently, these perceptions could also promote less favorable attitudes toward their integration within society, endorsing policies that limit the rights and opportunities granted to the ethnic minority (Gregurović, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A question may arise: Are adolescents more or less inclusive than their elders? In this regard, some pieces of evidence suggested that young people are generally more tolerant than adults (Dalton, 2015; Milkman, 2017) and perceive individuals with a migrant background more as strengths rather than threats to their countries (Gregurović, 2021). Conversely, other findings suggested that prejudice against ethnic minorities has increased compared to the past, stating that the new generations are less tolerant than the previous ones, especially toward foreign and immigrant workers (Hjerm, 2009; Janmaat & Keating, 2019; Keating & Janmaat, 2020).…”
Section: The Country Level: Approaches To the Integration Of People W...mentioning
confidence: 99%
See 1 more Smart Citation